Different Demand Response Programs with its Implementation in Various Countries and the Role of TOU DR in the Context of Nepal - Sapkota, Madhav; Karki, Rajesh; Karki, Nav Raj (International Journal on Engineering Technology, 2024)
With the increasing trend of electricity consumption worldwide, it creates a cumbersome, reliable power system and necessitates the construction of new generator companies, transmission lines, and other infrastructures. Despite investing in new infrastructures to manage occasional peaks, utilities can use the demand response concept to effectively handle demand during such peak time intervals, and in doing so, it enhance the grid stability. This assists in balancing the supply and demand for electricity, making the grid more resilient to fluctuations, and reducing the risk of blackouts. This paper delves into the diverse DR programs across different countries and comparative analysis for finding the suitable DR method to make a more reliable electric power network in Nepal.